HAK WANITA DALAM BEKERJA - Evy Savitri Gani (IAIN Ambon, 2017)
The number of female workers increased from year to year quite. International labor organization (ILO) recorded a growth in the number of female workers is increasing annually. In 2015, 38 percent of the 120 million workers in Indonesia are woman. Of the number of female workers workers increased sharply, many do not know their rights in the rights work. Rights of woman in work which is a form of legal protection granted by the state againts female workers is set in law number 13 of 2003 on employment among others : protection of working hours, the protection during maternity leave, giving the location of breastfeeding, protection of the health and safety of woman, and wage protection. For employers who do not provide the rights mentioned above will be liable to administrative sanctions, civil and criminal. Key words: rights, woman, work